Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru - Baihaqi, Moh. Hamdan (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
Principals, as educational leaders, have the responsibility to improve the Performance of the teachers in their schools. The head of the school must have an excellent strategy to improve teachers' Performance. The strategy is undertaken with the guidance of discipline, motivation and reward (award), the formation of Teachers ' Associations Field Studies, seminars, the classroom (class visits), and conduct an evaluation periodically. This study aims to determine how the Performance of teachers in high school Hidayatut Thullab Petuk Puhrubuh Semen Kediri; and the strategy of the head of school to improve teachers' Performance. The subjects of this study are Islamic senior high School plus Hidayatut Thullab Pethuk Puhrubuh Semen Kediri. The results showed the Performance of High School teachers of Islam plus Hidayatut Thullab Pethuk Puhrubuh semen Kediri corresponding duties and responsibilities.